CONVERSION OF PINEAPPLE PEEL GLUCOSE INTO BIOETHANOL USING SIMULTANEOUS SACCHARIFICATION AND FERMENTATION (SSF) METHOD AND SEPARATE HYDROLYSIS AND FERMENTATION (SHF) METHOD - Saragih, Hasri Tri Maya; Sembiring, Jhony Hartanta; Ginting, Elfrida (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2023)
This study aims to determine the bioethanol yield and characteristics from pineapple peel with two methods such as Simultaneous Saccharification and Fermentation (SSF) and Separate Hydrolysis and Fermentation (SHF). The percent yield of bioethanol produced from the fermentation of pineapple peel (Ananas comosus) with the Simultaneous Saccharification and Fermentation method was 63.50%, while the yield of bioethanol from the Separate Hydrolysis and Fermentation method was 58.75%. The physical characteristics of bioethanol pineapple peel waste using Simultaneous Saccharification and Fermentation method has a density of 0.8237 w/v whilst with Separate Hydrolysis and Fermentation is 0.8858 w/v. Furthermore, viscosity of bioethanol using Simultaneous Saccharification and Fermentation is 1.05 Cp whereas using Separate Hydrolysis and Fermentation is 1.02 Cp. Pineapple peel bioethanol method of Simultaneous Saccharification and Fermentation has concentration of 13% while Separate Hydrolysis and Fermentation method has concentration of 7.92%. FTIR spectra from SHF bioethanol missing the peak correlated with CH, CH3, and CO. These missing peaks is due to the high percentage of water. Furthermore, bioethanol from SSF method showed peaks corresponding to CH, CH3, and CO functional groups. It can be concluded that SSF method give bioethanol with optimum result.